PENGEMBANGAN INSTRUMEN TES TERTULIS BERBASIS PENDEKATAN SAINTIFIK PADA MATERI SISTEM GERAK KELAS XI SMA - Indah Aida Fatihah; Wan Syafi’i; Arnentis Arnentis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to develop a written test instrument based on scientific approach of the topic motion system on 11th grade in senior high school in October 2019-January 2020. The research was conducted in two places, for validation and phase I limited trials conducted at Biology Education Campus FKIP UNRI and the test phase II limited trials were conducted at SMAN 8 Pekanbaru. This type of research refers to the R&D research approach using the ADDIE model developed by Dick and Carry. The subject of this research is the subject matter of Biology on 11th grade in senior high school KD 3.5. The written test instrument developed consisted of 5 meetings with an allocation of 15 minutes for posttest work and 2x45 minutes (2 JP) for daily test questions. The parameters of this study include the results of the validation of the development of a written test instrument by the validator and the response of the limited phase I and phase II trial evaluations. The assessment is done using a validation sheet and a questionnaire. Data analysis is descriptive qualitative and quantitative. The results of this study indicate the written test instruments that have been developed are in the category of very valid with an average score of all aspects of 3.41, the value of the results of the limited trial phase I on all aspects obtained an average score of 3.35 and stage II 3.33 with very good categories . The results of theanalysis of the whole items of the test instrument from posttest 1 to daily tests in phase I trials obtained a reliability index of 0.837 to 0.939 in the very high category, a difficulty level index of 0.143 to 0.857, a difficult to easy category, a distinguishing power index at intervals of 0.40-1, 00 categories of questions are well received, and the percentage of effective deceiters is 70% -100%. While the results of the analysis of the whole item test instruments from posttest 1 to daily tests in phaseII trials obtained a reliability index of 0.685–0.923 categories of high to very high, difficulty index index of 0.138–0.758 categories of difficult to easy, distinctive power index at intervals of 0.40 -1.00 question categories were well received, and the percentage of deceiters was effective at 100%. Based on the results of the validation, the results of the limited trial phase I, the limited trial results phase II, and the revisions that have been made, this written test instrument is good and feasibleto be used as an evaluation tool in learning based on the scientific approach at school to hone and assess problem solving skills by students.KeyWords: Written Test Instrument, Scientific Approach, Motion System